EPC Minutes 2005-03-10 - Academic Senate:::::::::
Educational Policies Committee. Minutes of 9/24 – Approved. Agenda – Approved. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Student Affairs Report. EPC Report. FSAC Report. Associated Students Report. SAC Report. CFA Report. Ratification of faculty members on WASC Steering Committee -Approved. Revision to Biology concentration – Zoology approved for Senate consent calendar. WASC recommendations discussion. Faculty Retreat Topic discussion. Senate agenda approved.